Social Support and Academic Satisfaction in Calligraphy Learning: Evidence from Upper Primary School Students in the Context of Double Reduction Policy - Zhe Dong; Kou Heung; Zhongzhi Pan; Dong Wang; Jingjing Wang (Ilmu Inovasi Nusantara, 2026)
In the context of China’s “double reduction” policy, calligraphy education has gained increasing attention as an essential medium for preserving and transmitting traditional Chinese culture at the primary education level. Despite this growing emphasis, the implementation of calligraphy instruction in elementary schools still faces several challenges, including low student motivation, limited engagement in classroom activities, unsatisfactory learning experiences, and relatively low academic satisfaction. These issues indicate that instructional methods do not solely influence students’ learning success, but are also influenced by external environmental factors, particularly social support. Nevertheless, empirical studies examining the relationship between social support and academic satisfaction in primary school calligraphy education remain limited. Therefore, this study aims to analyze the influence of social support on the academic satisfaction of upper-grade primary school students participating in calligraphy learning. The study employed a quantitative survey design involving 518 fifth- and sixth-grade students from five primary schools in X City, China. Data were collected via questionnaires and analyzed using SPSS version 25.0. The findings revealed that students generally perceived social support at an above-average level and demonstrated high levels of academic satisfaction. Furthermore, the analysis indicated a significant positive correlation between social support and academic satisfaction. Social support was also found to significantly predict students’ academic satisfaction. These findings suggest that support from families, schools, and peers plays a crucial role in enhancing students’ learning experiences and overall satisfaction in calligraphy education. The study implies the importance of establishing a collaborative family–school–community support system to create a more positive and supportive learning environment, thereby improving students’ academic satisfaction and the overall quality of calligraphy education